Improving Writing Ability of The Tenth Graders Through Guided Question Technique - Masruroh, Lailatul; ArinalHaqq; Mazidah, Eva Nur (Universitas Terbuka, 2023)
The aim of this research is to improve writing ability of the tenth graders through guided question technique at MA Matlabul Huda in second semester academic year 2022-2023. The objective of the research was to find out the improvement writing ability through quided question technique in term of content and organization. This research consisted of two cycles, Each cycle consisted of two meeting there are : planning, acting on the plan, observing the action and reflecting on the observation. The subjects of the research were 8 students of tenth grade at MA Mathlabul Huda. to collect data, the writer used observation, questionnaire and test. The result of analysis showed that there was enhancement between cycle 1 to cycle 2. In the firts cycle the mean score was 67,5. it still low or under the criteria of success. In the second cycle students accomplished the lowest required passing grade, as well as reached the mean score 80,5. Therefore, the students attained the criteria of the success after the implementation of the action on the second cycle